Sistem Informasi Manajemen Dokumen Akreditasi Program Studi di Jurusan Teknik Informatika - Julianto, Afis; Supria; Enda, Depandi; Rahmadhani, Ayu; Rimanda, Suhardianto; Juelon Sinaga, Ali; Rizki Ramadhan, Ikhsan; Abidin, Zainal (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The accreditation process for study programs is an important step in ensuring the quality of higher education, which requires systematic and efficient management of accreditation documents. In the Department of Informatics Engineering, accreditation document management is still carried out manually, often causing difficulties in searching, storing, and coordinating between teams compiling forms. This study aims to design and develop a web-based accreditation document management information system that can facilitate the management, search, and monitoring of accreditation documents in accordance with BAN-PT or LAM INFOKOM standards. This system is designed to support multiple study programs to improve the effectiveness and efficiency of the accreditation process. With the implementation of this system, it is hoped that the accreditation process for study programs in the Department of Informatics Engineering can run faster, more structured, and more integrated.